UNSUR RUPA DAN MAKNA PADA BUSANA PENGANTIN BETAWI - Woelandhary, Ayoeningsih Dyah (LPPM Universitas PGRI Adi Buana Surabaya, 2019)
Bridal dress is found in all cultures in the archipelago, its existence is often used as a focal pointfor invited guests, so it is not surprising that fashion is one of the elements that most brides payattention to. Variety of designs and modifications are made by designers and brides to wear,but ingeneral the basic form is not removed, it is manifested in maintaining the spirit of culturalvalues embedded in it. The focus of this research is the Betawi regional wedding dress. ThisBetawi tribe is a tribe whose majority of the population used to be people who lived and settledin this region since the time of the formation of Batavia, they grew up and developed as a largeethnic group, the result of intermarriages and mixed marriages of various ethnic migrants.The form of acculturation can be seen in the designation of the clothes worn by the bride andgroom, namely the wedding dress 'haji care' for the bride and groom, and the